2019
DOI: 10.1111/jnc.14683
|View full text |Cite
|
Sign up to set email alerts
|

Pink1 regulates FKBP5 interaction with AKT/PHLPP and protects neurons from neurotoxin stress induced by MPP+

Abstract: Loss of function mutations in the PTEN‐induced putative kinase 1 (Pink1) gene have been linked with an autosomal recessive familial form of early onset Parkinson's disease (PD). However, the underlying mechanism(s) responsible for degeneration remains elusive. Presently, using co‐immunoprecipitation in HEK (Human embryonic kidney) 293 cells, we show that Pink1 endogenously interacts with FK506‐binding protein 51 (FKBP51 or FKBP5), FKBP5 and directly phosphorylates FKBP5 at Serine in an in vitro kinase assay. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 54 publications
0
29
1
Order By: Relevance
“…In the brain, PINK1 has shown diverse cytoprotective effects. Cellular depletion of PINK1 triggers neuronal cell death, possibly through complex interactions with several client proteins including Akt (14). PINK1 deficiency also leads to reduced dopamine levels, essential for coordinated motor function, and triggers synaptodendritic shrinkage (13,15,16) and the release of inflammatory cytokines such as TNF-α, IL-1β, and COX-2 by astrocytes and microglia, and after injury in the brain (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, PINK1 has shown diverse cytoprotective effects. Cellular depletion of PINK1 triggers neuronal cell death, possibly through complex interactions with several client proteins including Akt (14). PINK1 deficiency also leads to reduced dopamine levels, essential for coordinated motor function, and triggers synaptodendritic shrinkage (13,15,16) and the release of inflammatory cytokines such as TNF-α, IL-1β, and COX-2 by astrocytes and microglia, and after injury in the brain (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…The serine-threonine kinase PINK1 has been extensively investigated since its discovery as an autosomal recessive PDcausing gene (Valente et al, 2004). PINK1 activates and interacts with PI3-kinase-Akt signalling to induce cell survival, mitochondrial integrity and stress resistance (Akundi et al, 2012;Boonying et al, 2019;Contreras-Zárate et al, 2015;Ellis et al, 2013;Hauser et al, 2017;Maj et al, 2010;Mei et al, 2009;Murata et al, 2011;O'Flanagan et al, 2015;O'Flanagan and O'Neill, 2014;Sánchez-Mora et al, 2012;Soutar et al, 2018). Notably, Akt activity is significantly reduced in both in vitro PD models and human dopaminergic substantia nigral neurons in individuals with PD (Malagelada et al, 2008;Timmons et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…While it is clear that PINK1 can activate Akt (Akundi et al, 2012;Boonying et al, 2019;Contreras-Zárate et al, 2015;Ellis et al, 2013;Hauser et al, 2017;Maj et al, 2010;Mei et al, 2009;Murata et al, 2011;O'Flanagan and O'Neill, 2014;Sánchez-Mora et al, 2012;Soutar et al, 2018), and that PINK1 deletion reduces Akt activation, the mechanism by which this occurs and its dependence on PINK1 kinase activity remain unclear. Initial studies revealed that PINK1 markedly enhanced the phosphorylation of Akt at Ser 473 but not Thr 308 , inducing Akt activation that was essential for protection from a variety of cytotoxic agents (Murata et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Originally, it was inferred from the pattern of this protein in 2D gel electrophoresis and the modulation of this pattern by the use of kinase inhibitors or phosphatases [40][41][42]. More recently, PTEN-induced putative kinase 1 (PINK1) was found to phosphorylate FKBP51 at yet to be mapped serine residues [43]. Thereby, PINK1 regulates the interaction of FKBP51 with the kinase Akt1 and the phosphatase PHLPP [43].…”
Section: Post-translational Modificationsmentioning
confidence: 99%
“…More recently, PTEN-induced putative kinase 1 (PINK1) was found to phosphorylate FKBP51 at yet to be mapped serine residues [43]. Thereby, PINK1 regulates the interaction of FKBP51 with the kinase Akt1 and the phosphatase PHLPP [43]. This interaction further is controlled by acetylation of FKBP51 at lysines 28 and 155 [44].…”
Section: Post-translational Modificationsmentioning
confidence: 99%